Effects of seed treatment and foliar fertilisation by chelated fertilisers on the productivity of sugar beets (Beta vulgaris L.) - S. Kalenska; B. Mazurenko; N. Novytska; V. Melnychenko (Рослинництво та ґрунтознавство, 2025)
Sugar beets are a highly productive crop that requires a significant amount of micronutrients and trace elements. They are sensitive to a lack of micronutrients in the early stages of development, which can affect the morphological changes in the root crop and, consequently, reduce yield. The purpose of this study was to determine the effects of seed treatment with a complex of chelated fertilisers and the effects of foliar feeding on the biometric indicators of sugar beets, photosynthetic productivity, and technological qualities. The study was conducted on typical low-humus chernozems in the Right-Bank Forest-Steppe zone of Ukraine. To determine the mass of roots and leaves, leaf area, and photosynthetic productivity, samples were taken during the row closure phase, the mid-phase of intensive root growth, and the row reopening phase. Technological qualities, root yield, and sugar content were determined in plants selected at the physiological maturity phase. The study found that foliar feeding significantly increased root mass during the row reopening phase and physiological maturity. The highest root mass was formed in the seed treatment variant with a high content of trace elements and foliar feeding. The root mass reached 692 g with a yield of 59.6 t/ha and a sugar content of 16.6%. Technological indicators, particularly sugar yield for this variant, were also maximal at 9.86 t/ha. Nanofertilisers for foliar feeding enabled an increase in leaf area until the row reopening phase without reducing net photosynthetic productivity, which allowed the crops to accumulate more dry matter. Seed treatment with chelated fertilisers increased the accumulation of dry mass in the early stages, leading to a larger photosynthetic apparatus, which collectively resulted in increased productivity